2023
DOI: 10.1186/s13054-023-04350-8
|View full text |Cite
|
Sign up to set email alerts
|

Lung morphology impacts the association between ventilatory variables and mortality in patients with acute respiratory distress syndrome

Abstract: Background Acute respiratory distress syndrome (ARDS) patients with different lung morphology have distinct pulmonary mechanical dysfunction and outcomes. Whether lung morphology impacts the association between ventilatory variables and mortality remains unclear. Moreover, the impact of a novel combined ventilator variable [(4×DP) + RR] on morality in ARDS patients needs external validation. Methods We obtained data from the Chinese Database in Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The beneficial effect of personalized ventilation in the LIVE study was masked by the large proportion of patients with misclassified lung morphology, an issue that the PEGASUS study aims to address [ 8 ]. Findings from a recent retrospective study support the distinct tidal volume targets for the “focal” and “non-focal” subphenotype, as this study found an association between driving pressure and mortality in “non-focal” patients, but not in “focal” patients [ 25 ].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The beneficial effect of personalized ventilation in the LIVE study was masked by the large proportion of patients with misclassified lung morphology, an issue that the PEGASUS study aims to address [ 8 ]. Findings from a recent retrospective study support the distinct tidal volume targets for the “focal” and “non-focal” subphenotype, as this study found an association between driving pressure and mortality in “non-focal” patients, but not in “focal” patients [ 25 ].…”
Section: Discussionsupporting
confidence: 55%
“…Several studies support the rationale behind the ventilation strategies for the “focal” and “non-focal” ARDS subphenotypes [ 7 , 8 , 25 ]. Patients with “non-focal” ARDS showed to respond better to recruitment maneuvers in comparison to patients with “focal” ARDS in an observational study.…”
Section: Discussionmentioning
confidence: 97%
“…(8) Findings from a recent retrospective study support the distinct tidal volume targets for the "focal" and "non-focal" subphenotype, as this study found an association between driving pressure and mortality in "non-focal" patients, but not in "focal" patients. (25) A major strength of the present study is the use of LUS to assess lung morphology, as it is a widely available, bedside, non-invasive technique that can accurately classify lung morphology compared to gold standard chest CT.(16)(26) A second advantage is that the ventilation strategies in both study arms are highly standardized and feasible. The personalized strategy is based on the LIVE study, while the conventional strategy is based on the latest ESICM guidelines for respiratory support in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Speculation on failing to show the benefits of higher PEEP is that none of these trials has been effective in assessing lung recruitability [ 19 ]. According to the morphological characteristics of lung lesions, ARDS can be classified into focal and non-focal as assessed by chest CT [ 20 , 21 ]. Patients with focal ARDS have a lower amount of potentially recruitable lung and higher lung compliance.…”
Section: Introductionmentioning
confidence: 99%